Ultrasonic treatment improves the performance of starch as depressant for hematite flotation - Ming Zhang; Zeping Xu; Lei Wang (Ultrasonics Sonochemistry, 2022)
In this study, ultrasonic treatment was introduced to enhance the depressive performance of starch in the reverse flotation separation of fine hematite from quartz. It was found that after ultrasonic treatment, starch was not only able to impart a higher surface wettability of hematite, but also better reduced the degree of entrainment of fine hematite, both of which alleviated the loss of hematite to the froth. Flocculation tests together with starch property characterization were conducted to understand the underpinning mechanism. It is interesting that ultrasonic treatment of starch led to stronger and more selective flocculation of hematite, which accounted for the reduced entrainment loss of fine hematite and benefited the concentrate Fe grade. It was also found that ultrasonic treatment enhanced the dissolution and acidity of starch with a simultaneous increase in the content of amylose, which in turn could contribute to the improved depression and selective flocculation of hematite.